2017
DOI: 10.1352/1934-9556-55.5.325
|View full text |Cite
|
Sign up to set email alerts
|

Mothers Parenting a Child With Intellectual Disability in Urban India: An Application of the Stress and Resilience Framework

Abstract: We examined relevance of the key constructs of the stress and resilience framework in the urban Indian context. Analyses of interviews with urban Indian mothers (N = 47) of a 3-6 year old child with intellectual disability generated themes on maternal appraisals of the child's disability, perceived stressors, and resources. Mothers seemed to utilize a combination of fact-based and religious explanation to make sense of their child's disability. Parental stressors ranged from child-related factors (diagnosis, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
7
19
0
Order By: Relevance
“…The formula is utilized to calculate the score of practice teaching evaluation, according to the results of student evaluation to conduct targeted counseling for students, and promote the cultivation of students' practical ability (Akre and Suris, 2017;John and Zapata Roblyer, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…The formula is utilized to calculate the score of practice teaching evaluation, according to the results of student evaluation to conduct targeted counseling for students, and promote the cultivation of students' practical ability (Akre and Suris, 2017;John and Zapata Roblyer, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…However, it has also been suggested that factors such as adaptive coping strategies, perceived social support and a positive evaluation of the disability of the child contribute to the individual. 51 Th e fact that there is no control group, and that the disabled children do not have the same diagnoses was the most important limitation of the study. Causality relationships could not be discussed because of the cross-sectional nature of the study.…”
Section: Discussionmentioning
confidence: 99%
“…In project cooperation, enterprises and individual students will form employment relationship. In cultivation of medical college students' employability, innovation and entrepreneurship education should pay attention to construction of enterprise participation model (Zhang, 2017;John et al, 2017).…”
Section: Focus On Implementation Of Enterprise Participation Modelmentioning
confidence: 99%